2017
DOI: 10.1016/j.physd.2017.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Standing and travelling waves in a spherical brain model: The Nunez model revisited

Abstract: The Nunez model for the generation of electroencephalogram (EEG) signals is naturally described as a neural field model on a sphere with space-dependent delays. For simplicity, dynamical realisations of this model either as a damped wave equation or an integro-differential equation, have typically been studied in idealised one dimensional or planar settings. Here we revisit the original Nunez model to specifically address the role of spherical topology on spatio-temporal pattern generation. We do this using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 53 publications
1
43
0
Order By: Relevance
“…The double-digits numerical subscripts in Eq (27) refer to the row-column element of the respective matrix. Eq (27) can be used to compute the separate harmonic and temporal power spectra of the model, as well as the correlation and functional connectivity matrices (Methods Eq (77)).…”
Section: Wilson-cowan Model Chaossmentioning
confidence: 99%
See 2 more Smart Citations
“…The double-digits numerical subscripts in Eq (27) refer to the row-column element of the respective matrix. Eq (27) can be used to compute the separate harmonic and temporal power spectra of the model, as well as the correlation and functional connectivity matrices (Methods Eq (77)).…”
Section: Wilson-cowan Model Chaossmentioning
confidence: 99%
“…Eq (27) and (28) represent a general result that does not only apply to the Wilson-Cowan model. In fact, these equations describe the harmonic-temporal and harmonic power spectra of stochastic equilibrium fluctuations for the first population of any graph neural field model with two interacting populations and a first-order temporal differential operator.…”
Section: Wilson-cowan Model Chaossmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, it is not clear that our results will carry over to the full system (6). In principle we could linearise (6) about a steady state of (14) to determine its stability, but the resulting calculations seem significantly more difficult than those in [64,42,41] (where only one spatial dimension is considered) and [61] (in which only the stability of a spatially uniform state is considered) and we do not pursue this further. However, numerical solutions on the full sphere (using the scheme presented below) indicate that the double spot solution in Fig.…”
Section: Numerical Continuationmentioning
confidence: 99%
“…For example in the Nunez model [10] for the generation of the α-rhythm neuronal cell types are arranged in sheets, with no representation of dendritic processing. A recent study of standing and traveling waves in the Nunez model posed on a sphere can be found in [11]. Interestingly the Nunez model has a representation of space-dependent delays arising from the finite speed of action potential propagation along axons, and for certain patterns of decaying strength of non-local connectivity it can be formulated as a damped inhomogeneous wave equation [12].…”
Section: Introductionmentioning
confidence: 99%